2014
DOI: 10.1007/s10753-014-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Activity of a Monomeric Smac Mimetic on Human Fibroblast-Like Synoviocytes from Patients with Rheumatoid Arthritis

Abstract: Inhibitors of apoptosis proteins (IAPs) block cell death in response to diverse stimuli. The mitochondrial protein, second mitochondria-derived activator of caspase (Smac), negatively regulates IAP inhibition of caspase activity. We investigated the proapoptotic activity of a synthetic Smac (Smac 066) on fibroblast-like synoviocytes (FLS) derived from patients with active rheumatoid arthritis (RA). We found that Smac 066 induced significant apoptosis in all RA-FLS samples. Furthermore, IAPs, which are upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…IAPs can regulate apoptosis by directly binding to and preventing downstream effector functions of caspase 3, caspase 7 and caspase 9, thereby blocking the assembly of caspase 8 and caspase 10 155,156 . In response to a pro-apoptotic stimulus, the diablo homolog, mitochondrial (also known as second mitochondria-derived activator of caspases (Smac)) can be liberated from the mitochondria and translocate into the cytoplasm to block the anti-apoptotic activity of IAPs 157,158 .…”
Section: Extrinsic Pathway Of Apoptosis In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…IAPs can regulate apoptosis by directly binding to and preventing downstream effector functions of caspase 3, caspase 7 and caspase 9, thereby blocking the assembly of caspase 8 and caspase 10 155,156 . In response to a pro-apoptotic stimulus, the diablo homolog, mitochondrial (also known as second mitochondria-derived activator of caspases (Smac)) can be liberated from the mitochondria and translocate into the cytoplasm to block the anti-apoptotic activity of IAPs 157,158 .…”
Section: Extrinsic Pathway Of Apoptosis In Ramentioning
confidence: 99%
“…A number of compounds have been designed to mimic the structure of these molecules. Smac mimetics bind specifically to three IAPs, including E3 ubiquitin-protein ligase XIAP, Baculoviral IAP repeat-containing protein 2 (also known as C-IAP1) and Baculoviral IAP repeat-containing protein 3 (also known as C-IAP2) 155 . One such Smac mimetic downregulates XIAP, C-IAP1 and C-IAP2 and can induce cell death in apoptosis-resistant RA fibroblast-like synoviocytes, thereby implicating this molecule as a local therapeutic for RA 155 .…”
Section: Extrinsic Pathway Of Apoptosis In Ramentioning
confidence: 99%
“…Lattuada D found that SMAC was associated with caspase 8 and caspase 3 activities, and induced signi cant apoptosis in all RA-FLS samples. In addition, SMAC signi cantly upregulated IGFBP-5, a protein involved in differentiation, apoptosis, and osteoblastic activation, so they included that SMAC may represent a new therapeutic approach to RA treatment 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cellular IAP1 (cIAP1) and cellular IAP2 (cIAP2) are unable to directly inhibit caspases and instead promote prosurvival signaling from TNF receptor (TNFR)1 complex I and limit formation of the apoptosis-inducing TNFR1 complex II [193195]. In response to pro-apoptotic stimuli, the second mitochondria-derived activator of caspases (Smac) can be liberated from the mitochondria into the cytoplasm to block the anti-apoptotic activity of IAPs [196, 197], and a number of compounds designed as therapeutic targets imitate the structure of these molecules (Smac mimetics) [191]. …”
Section: Programmed Cell Death Pathways In Dendritic Cells and Macmentioning
confidence: 99%